Public expenditure on infrastructural development and economic growth: Evidence from Nigeria - Anderu, KEJI Sunday; Tosin, KEJI Oluwaseun (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This research investigated the nexus between public spending on infrastructural development and economic growth: evidence from Nigeria. As a matter of urgency, there is a need for the Nigerian government to invest in infrastructure for sustainable economic growth since infrastructural development touches all human fields of endeavors in one way or another. Notably, despite the country’s pole position in the economic ranking in Africa, Nigeria’s infrastructural state still falls short, which has led to negative economic growth in recent years. Therefore, it is pertinent in this study to unravel the causes and the missing gaps between increasing fiscal spending on infrastructure and slow economic growth in Nigeria. Interestingly, Autoregressive Distributed Lags and cointegration techniques were adopted to investigate whether there are long interactions between economic advancement and public funding of social amenities in the case of Nigeria. Furthermore, post-estimation tests were carried out to ascertain the validity of the models adopted in the study. The investigations from the study showed that short and long-run nexus subsists between government investment in infrastructure and economic growth in Nigeria. Hence, to address the problems underpinning this research, the study recommended that a proactive policy framework be used to promote economic growth via a redesigned fiscal framework in Nigeria. Also, protective laws and acts to safeguard the existing infrastructures should be well-pronounced and adopted by policymakers to expand the productive life span of social goods.